Definition and Characteristics of “Cyberbullying” among Vietnamese Students - Tran, Cong Van (H. : ĐHQGHN, 2019)
The purpose of the present study was to define the term “cyberbullying” from the perspective of middle- and high-school students in Vietnam, detailing its characteristics. The study used qualitative focus groups with Vietnamese students, teachers, parents, school psychologists, and psycho-educational experts in Hanoi, Vietnam. From the perspective of these informants, cyberbullying involves seven characteristics: (a) The indirect transmission of negative, untrue, hateful, and/ or secret, personal information through electronic devices and applications, (b) with the intention to hurt the victim, (c) which may or may not be part of a series of repetitive actions that nonetheless may have ongoing effects, (d) with the perpetrator an individual or a group, (e) in the context of a power imbalance relationship, (f) with the perpetrator(s) able to hide his or her identity, (g) and the bullying able to occur at all times in any place the victim has internet access.